Prolactin concentrations in ovulatory but infertile women: treatment with bromocriptine. Issue 6096 (5th November 1977) - Lenton, E A; Sobowale, O S; Cooke, I D
Abstract : We measured basal plasma prolactin concentrations (in samples obtained during the early follicular phase) in 25 normal (control) women and in a similar group of 40 patients with a long-standing history of infertility. The infertile patients were all ovulating regularly, and had been unsuccessfully treated with clomiphene and in some cases dydrogesterone and human menopausal gonadotrophin. Although none of the patients had plasma prolactin concentrations greater than 1000 muU/ml, 47.5% of the estimations were greater than 1 standard deviation (SD) above the mean established for our control group. This difference was highly significant (P less than 0.001). Treatment with various bromocriptine regimens effectively reduced prolactin concentrations to below normal in all cases, and 16 pregnancies followed-13 during bromocriptine treatment and three in the first post-treatment cycle. The cumulative conception rate was 63.4% after 10 months' treatment.